Mixed Cropping Studies for Increased Returns in Upper Damodar Valley - Vasudevaiah, R. D.; Bhattacharya, J.; Teotia, S. P. Singh (Journal of Soil and Water Conservation, 2022)
Upper Damodar Valley comprises a total land area of 4.40 million acres out of which 1.47 million acres, having within it 0.80 million acres (57.0%) farm lands, need intensive soil conservation measures. It has been estimated that soil loss from overgrazed lands under faulty practices or management is up to a tune of 12 Acft. per square mile and from shrubby lands with grazing it is 7.5 Acft per square mile. If this soil loss is allowed to continue unabated the top soil is liable to be lost within 35 - 60 years. In order to mini-mise this heavy soil loss the Soil Conservation Department of Damodar Valley Corporation has taken up an extensive programme of terracing on uplands.